PENGARUH TRAVEL RISK PERCEPTION TERHADAP TOURIST INTENTION MELALUI TRAVEL ANXIETY DI CV. WISATA OUTBOUND INDONESIA - Permadi, Inayati; Yuniawati, Yeni; Pandia, Suka Prayanta Pandia (JURNAL MEKAR, 2024)
This quantitative study aims to analyze the effect of travel risk perception on tourist intention, with travel anxiety as a mediating variable, in the context of adventure tourism at CV. Wisata Outbound Indonesia. Using a descriptive and verificative approach, data were collected from 189 respondents via an online survey, with a Likert-scale questionnaire measuring key variables. Path analysis was employed to examine both the direct and indirect effects of travel risk perception on tourist intention. The results show that travel risk perception, which includes environmental risks such as weather conditions, service risks like safety measures, and physical and health risks related to injuries, has a significant positive effect on travel anxiety, with a path coefficient of 0.884. Additionally, travel anxiety negatively impacts tourist intention, with a path coefficient of -0.704, decreasing the likelihood of participating in adventure tourism activities. The overall effect of travel risk perception on tourist intention, mediated by travel anxiety, accounts for 93.6% of the variance (R² = 0.936). These findings demonstrate that higher levels of perceived travel risk lead to increased anxiety, which significantly reduces tourist intention. The research highlights the importance of addressing perceived risks and travel anxiety in order to influence tourist decisions positively. Tourism service providers are advised to enhance risk management and safety communication strategies to mitigate anxiety and increase tourist participation, particularly in high-risk activities like adventure tourism.